Open-Source Code-Based Tidal Modeling of Tropical and Temperate Waters - Srikanth, Narasimalu; Kannappan, Lakshmanan (Frontiers in Energy Research, 2021)
Tidal energy is the most reliable and predictable form of energy. Many developing countries are prone to energy self-sufficiency due to lack of tidal data , expensive commercial tidal modelling tools and program codes. Thus, the present study focuses on use of an open source finite element code and open source input data for tidal prediction so that it can be easily adopted by such developing countries. The thrusting force behind the coastal dynamics is mainly from tides, their interactions and on the seabed profile. The seabed roughness profile creates a drag force on the flow on the velocity field. Lack of understanding on effects of seabed friction on tidal modelling might reduce the accuracy of model prediction. Thus, the present study also focuses on the effects of seabed roughness on tidal prediction using the open source finite element based 2-dimensional depth average model. From the results, it can be found that increase in seabed friction reduces the flow velocity and thus the average power density of the location. Hence, it is important to optimize the seabed roughness of the location and include in the models in order to obtain accurate tidal prediction. Currently, most of the tidal modelling studies has been done for countries on temperate climate while not much studies have been done on tropical climate countries which are especially in the tropical belt. Thus, the present study would also focus on comparison of tidal models of two sites – Alderney Race (Temperate country) and Singapore (Tropical country). The suitability of the open source code would be studied and compared between the two sites.